APPLICATION OF CAUSAL ANALYSIS OF DISRUPTIONS AND THE FUNCTIONAL RESONANCE ANALYSIS METHOD (FRAM) IN ANALYZING THE RISK OF THE BAGGAGE PROCESS - Anna KWASIBORSKA; Krzysztof KĄDZIOŁA (Scientific Journal of Silesian University of Technology. Series Transport)
Following the events related to the pandemic and the war in Ukraine, increasing air traffic also increases turnaround agents' activity at airports. Turnaround operations are among the critical activities performed at airports, which must be characterized by punctuality and accuracy of the elementary handling operations. Lack of punctuality in ground handling causes delays in air traffic. On the other hand, a lack of accuracy can also cause disruptions that can turn into aviation incidents. Achieving punctuality and accuracy in aircraft handling is possible by minimizing the resulting disruptions during such handling. The safety management system (SMS) assumes activities to reduce the causes of potential incidents. In the turnaround process, the human factor, the technical aspect, and compliance with existing procedures are significant. The authors have extensively analyzed the disruptions arising during ground handling, learning its causes and effects, which will help avoid adverse events. Occurring disruptions can cause delays in the execution of flight operations but can also cause aviation incidents. Therefore, the authors focused on ground-handling disruptions that can cause adverse aviation incidents. The article presents the interference analysis results as an Ishikawa diagram. Using the FRAM method, an analysis of possible disruptions during the baggage handling process was carried out.